Publishing under COVID-19 in small book markets - Kovač, Miha; Gudinavičius, Arūnas (Knygotyra, 2020)
The paper is based on a survey that was conducted among publishers in Slovakia, Iceland, Lithuania and Slovenia in May and August 2020. The paper looks at how publishers reacted to the COVID-19 crisis in their respective countries, what was its impact on book sales and how did the publishers adapt the production of new books to changed circumstances. In addition, the paper analyses changed attitudes of publishers towards e-books and other digital book formats that become more popular in lockdown times. The research revealed that COVID-19 lockdowns resulted in decreased sales of printed books in all four small book markets. However, sales of e-books and audiobooks slightly increased during that period. This increase in digital sales did not contribute significantly to overall results of book industries due to its small market share in all four countries.
Keywords: publishing; small book markets; COVID-19; pandemic